A cluster of children with facial nerve palsy in a high prevalence area for COVID-19 - David Barron; Owen Richards; Fleur Archer; Mohamed Abdelrazek; Rajesh Ranjan; Omotakin Omolokun (BMC, 2021)
Abstract Background COVID-19 is a disease of varying presentation and neurological sequelae of the disease are being studied. Following a cluster of paediatric facial nerve palsy (FNP) cases in an area of South Wales with a high prevalence of COVID-19, we conducted an opportunistic study to determine whether there has been an increase of incidence of FNP and if there is an association between the FNP and COVID-19 in children. Methods We performed a retrospective review of the incidence of FNP between 2015 and 2020 across two hospitals within the health board. The incidence was compared with that in 2020 including a cluster of six children in 14 weeks, presenting to Royal Glamorgan Hospital between June and October. Results There were 48 cases of children with FNP across both hospital within the study years. Seven (7) cases in 2020. The incidence was not statistically different in comparison to other years. Five out of six of these children in 2020 had antibody testing for COVID-19. All serology testing (100%) returned negative for SARS-CoV- 2 antibodies. Conclusions In high prevalence area for COVID-19, cases of children with FNP have not shown a commensurate increase. we have found no causal link between COVID-19 and FNP in children. While this is a small study, larger cohort studies are needed to support this finding. As new strains of COVID-19 are being reported in UK, South Africa and Brazil, physicians need to continue to be vigilant for consistent pattern of signs and symptoms, especially in children.